(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify the impact of the (Neale) model on the acquisition of scientific concepts among the second intermediate grade students, and the researcher adopted the experimental approach with an experimental design for two equal groups, and the researcher randomly chose (Al-Zahra Intermediate School for Girls), as the researcher chose Division (A) randomly to represent the experimental group that will be studied Science subject according to the (Neale) model, and Division (B) to represent the control group that will study the same subject in the usual way. The total number of female students in the two groups reached (60) students; (30) female students in the experimental group, and (30) female students in the control group; It was statistically rewarded between the members of the two groups in the following variables: (chronological age calculated in months, previous information test, grades of the previous year (2021-2022) in science subject, Raven IQ test), and the researcher identified the study subject with subjects from the science book for the second intermediate grade, then The researcher formulated behavioral goals, as they numbered (261) behavioral goals. As for the research tool, the researcher proceeded to build the test of acquiring scientific concepts, which consisted of (45) objective test items of the type of multiple choice of four alternatives, and the validity, discrimination coefficient and difficulty were verified. effectiveness of alternatives and stability; Its stability was verified by the split-half method. The researcher used the appropriate statistical methods to extract the data, and the results showed that the students of the experimental group outperformed the students of the control group in the test of acquiring scientific concepts.